Cause of death for patients with breast cancer: discordance between death certificates and medical files, and impact on survival estimates - Hava Izci; Tim Tambuyzer; Jessica Vandeven; Jérôme Xicluna; Hans Wildiers; Kevin Punie; Nynke Willers; Eva Oldenburger; Els Van Nieuwenhuysen; Patrick Berteloot; Ann Smeets; Ines Nevelsteen; et al. (BMC, 2021)
Abstract Background Registration and coding of cause of death is prone to error since determining the exact underlying condition leading directly to death is challenging. In this study, causes of death from the death certificates were compared to patients' medical files interpreted by experts at University Hospitals Leuven (UHL), to assess concordance between sources and its impact on cancer survival assessment. Methods Breast cancer patients treated at UHL (2009-2014) (follow-up until December 31st 2016) were included in this study. Cause of death was obtained from death certificates and expert-reviewed medical files at UHL. Agreement was calculated using Cohen's kappa coefficient. Cause-specific survival (CSS) was calculated using the Kaplan-Meier method and the relative survival probability (RS) using the Ederer II and Pohar Perme method. Results A total of 2862 patients, of whom 354 died, were included. We found an agreement of 84.7% (kappa-value of 0.69 (95% C.I.: 0.62-0.77)) between death certificates and medical files. Death certificates had 10.7% false positive and 4.5% false negative rates. However, five-year CSS and RS measures were comparable for both sources. Conclusion For breast cancer patients included in our study, fair agreement of cause of death was seen between death certificates and medical files with similar CSS and RS estimations.